Evaluating public health awareness and hygienic interventions amidst the COVID-19 outbreak: insights from three districts in Himachal Pradesh, India - Walia, Gurinder Kaur; Sharma, Richa; Chopra, Diksha (International Journal of Research in Medical Sciences, 2024)
Background: This study aimed to elucidate the awareness, knowledge, and adoption of COVID-19 prevention measures, including the utilization of masks, hand sanitizers, social distancing, proper sanitation, and adherence to lockdown protocols, among residents of Hamirpur, Bilaspur, and Mandi in Himachal Pradesh, India. With a particular focus on vaccination strategies, this research investigates the pivotal role of vaccination in curbing the spread of the pandemic and reducing the associated morbidity and mortality rates. Methods: A cross-sectional survey was conducted from April to May 2022, involving a structured questionnaire designed to assess environmental impacts, testing knowledge, public health behaviors, and vaccine perceptions. The survey sample included participants from diverse socio-economic backgrounds. Data were analyzed using descriptive statistics and inferential analysis to identify correlations between socio-educational factors and adherence to COVID-19 prevention measures. Results: The findings indicate a moderate level of awareness and knowledge around 93.76% about COVID-19 prevention measures among the residents. However, significant gaps were identified, particularly in understanding the importance of vaccination and proper sanitation practices. The analysis revealed that socio-educational factors significantly influenced public attitudes and behaviors towards COVID-19 prevention. Notably, lower socio-economic groups exhibited lower adherence to recommended health behaviors. Conclusions: The study underscores the critical need for targeted awareness campaigns to enhance public understanding of COVID-19 transmission, severity, and preventive measures. Educational initiatives should prioritize clear and accessible communication, especially for lower socio-economic groups, to mitigate the impact of the pandemic. Empowering communities with comprehensive knowledge is essential for effective public health management and reducing COVID-19 morbidity and mortality.